2020
DOI: 10.1093/gji/ggaa062
|View full text |Cite
|
Sign up to set email alerts
|

Marchenko multiple elimination of a laboratory example

Abstract: SUMMARY The Marchenko multiple elimination (MME) scheme is derived from the coupled Marchenko equations. It is proposed for filtering primary reflections with two-way traveltime from the measured acoustic data. The measured acoustic reflection data are used as its own filter and no model information or adaptive subtraction is required to apply the method. The data obtained after MME are better suited for velocity model construction and artefact-free migration than the measured data. We apply the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Later, Zhang and Slob [4] used a set of measured laboratory data to evaluate the performance of the MME. The same authors [5] showed the first example of applying the MME on a field data set from the Norwegian North Sea, which validated the capabilities of the MME schemes and showed that it could effectively eliminate internal multiples. Aiming to explore the potential of the MME approach, many techniques went on to be developed, such as the transmission-compensated Marchenko multiple eliminations (T-MME) derived by Zhang and colleagues [6], which is a scheme that eliminates multiple internal reflections and compensates for two-way transmission losses contained in primary reflections.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Later, Zhang and Slob [4] used a set of measured laboratory data to evaluate the performance of the MME. The same authors [5] showed the first example of applying the MME on a field data set from the Norwegian North Sea, which validated the capabilities of the MME schemes and showed that it could effectively eliminate internal multiples. Aiming to explore the potential of the MME approach, many techniques went on to be developed, such as the transmission-compensated Marchenko multiple eliminations (T-MME) derived by Zhang and colleagues [6], which is a scheme that eliminates multiple internal reflections and compensates for two-way transmission losses contained in primary reflections.…”
Section: Introductionmentioning
confidence: 79%
“…The Marchenko multiple eliminations based on Equation (4) are conventionally named by the MME scheme. However, we must remember that the solution based on the Neumann series approximation converges only if (5) Marchenko Multiple Eliminations Scheme…”
Section: Neumann Series Solutionmentioning
confidence: 99%
“…In that case, internal multiple reflections contained in input shot gather cannot be removed or attenuated effectively. The measured laboratory dataset used in Zhang and Slob (2019b) can be taken as an example. The MME scheme was applied to remove internal multiple reflections contained in the measured laboratory dataset, although some internal multiple reflections were successfully removed or attenuated, some internal multiple reflections were present with opposite polarity or even stronger after the processing because of the low-quality of the input dataset.…”
Section: Discussionmentioning
confidence: 99%
“…This simple model is chosen to keep the number of events limited and to allow for an explanation that can be followed more easily. The method is not limited to simple models and can successfully be applied to complicated 3D media as well (see for example Zhang and Slob (2020c)).…”
Section: Introductionmentioning
confidence: 99%